Safety and Biocompatibility of a New High-Density Polyethylene-Based Spherical Integrated Porous Orbital Implant: An Experimental Study in Rabbits. (24th November 2015) - Fernandez-Bueno, Ivan; Di Lauro, Salvatore; Alvarez, Ivan; Lopez, Jose Carlos; Garcia-Gutierrez, Maria Teresa; Fernandez, Itziar; Larra, Eva; Pastor, Jose Carlos
Abstract : Purpose . To evaluate clinically and histologically the safety and biocompatibility of a new HDPE-based spherical porous orbital implants in rabbits. Methods . MEDPOR (Porex Surgical, Inc., Fairburn, GA, USA), OCULFIT I, and OCULFIT II (AJL Ophthalmic S.A., Vitoria, Spain) implants were implanted in eviscerated rabbis. Animals were randomly divided into 6 groups (n = 4 each) according to the 3 implant materials tested and 2 follow-up times of 90 or 180 days. Signs of regional pain and presence of eyelid swelling, conjunctival hyperemia, and amount of exudate were semiquantitatively evaluated. After animals sacrifice, the implants and surrounding ocular tissues were processed for histological staining and polarized light evaluation. Statistical study was performed by ANOVA and Kaplan-Meier analysis. Results . No statistically significant differences in regional pain, eyelid swelling, or conjunctival hyperemia were shown between implants and/or time points evaluated. However, amount of exudate differed, with OCULFIT I causing the smallest amount. No remarkable clinical complications were observed. Histological findings were similar in all three types of implants and agree with minor inflammatory response. Conclusions . OCULFIT ophthalmic tolerance and biocompatibility in rabbits were comparable to the clinically used MEDPOR. Clinical studies are needed to determine if OCULFIT is superior to the orbital implants commercially available.